2005
DOI: 10.1007/s11171-005-0044-2
|View full text |Cite
|
Sign up to set email alerts
|

Primary Structures of Actinoporins from Sea Anemone Oulactis orientalis

Abstract: Partial amino acid sequences of the actinoporins Or-A (136 aa) and Or-G (144 aa) isolated from the Sea of Japan sea anemone O ulactis orientalis were determined by sequencing the clones obtained by the amplification of genomic DNA and cDNA with primers specific to the N -terminal regions of the O. orientalis actinoporin sequences and to the ë -terminal region, which is highly conservative in all the known actinoporin sequences. The complete structures of Or-A (165 aa) and Or-G (173 aa) were elucidated by seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…As already mentioned above, the method we employed for obtaining the soluble proteomes from unbleached and bleached specimens of M. complanata involved osmotic shock in bidistilled water, which causes the discharge of the nematocysts content [48]. Interestingly, in the present study we found that bleached hydrocorals had increased levels of two proteins that showed amino acid sequence similarity to the pore forming toxins (PFTs), echotoxin-2 and DELTA-actitoxin-Oor1b, which were previously identified in “giant triton” Monoplex parthenopeus (phylum Mollusca) and the “Sea of Japan anemone” Oulactis orientalis , respectively [117,118].…”
Section: Discussionmentioning
confidence: 50%
“…As already mentioned above, the method we employed for obtaining the soluble proteomes from unbleached and bleached specimens of M. complanata involved osmotic shock in bidistilled water, which causes the discharge of the nematocysts content [48]. Interestingly, in the present study we found that bleached hydrocorals had increased levels of two proteins that showed amino acid sequence similarity to the pore forming toxins (PFTs), echotoxin-2 and DELTA-actitoxin-Oor1b, which were previously identified in “giant triton” Monoplex parthenopeus (phylum Mollusca) and the “Sea of Japan anemone” Oulactis orientalis , respectively [117,118].…”
Section: Discussionmentioning
confidence: 50%
“…However, the existence of actinoporin combinatorial libraries and an isoforms ratio in them remain unclear. A few different isoforms, for most sea anemones, are shown to be usually produced by the same species in large enough amounts for detection and purification [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 27 ]. The combinatorial library of actinoporins in S. haddoni venom has not also been found; the authors have identified only one actinoporin, although, according to 2DE data, actinoporins were found in many different spots [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the actinoporins are produced as isoforms. Some of them, equinatoxins EqtI–EqtV from Actinia equina [ 9 , 10 , 11 ], magnificalysins HMgI–HMgIII and HmT from Heteractis magnifica [ 12 , 13 , 14 ], sticholysins StnI and StnII from Stichodactyla helianthus [ 15 ], actinoporins RTX-A, RTX-S, RTX-G, and RTX-SII from Heteractis crispa [ 16 , 17 , 18 ], cytolysins Or-A and Or-G from Oulactis orientalis [ 19 , 20 ], cytolysins Pstx-20A and Pst-I from Phyllodiscus semoni [ 21 , 22 ], and actinoporins Avt-I and Avt-II from Actineria villosa [ 22 , 23 ] are isolated and functionally characterized. However, there are a lot of actinoporin sequences that are deduced on the base of their genes.…”
Section: Introductionmentioning
confidence: 99%
“…The development of similar isotoxins with small functional differences might be an evolutionary strategy occurring in anemones to successfully explore the variety of preys encountered in the marine environment (Fatehi et al, 1994;Anderluh and Ma cek, 2002). Examples of anemones with different isoforms of the same actinoporin are: Actinia equina (Ma cek and Lebez, 1988;Anderluh et al, 1999), Actinia tenebrosa Galletis and Norton, 1990), S. helianthus , H. crispa (also called Radianthus macrodactylus) (Monastyrnaya et al, 2002;Klyshko et al, 2004), H. magnifica (Wang et al, , 2008, Oulactis orientalis (Il'ina et al, 2005a(Il'ina et al, , 2005bMonastyrnaya et al, 2010), A. fragacea , Actineria villosa, and Phyllodiscus semoni (Uechi et al, 2010). It is likely that these organisms produce a higher number of isoforms that will be discovered when large scale methods, such as cDNA or transcriptome library sequencing, are performed.…”
Section: Actinoporins Are Encode By Multigene Familiesmentioning
confidence: 99%
“…The complete amino acid sequences of RTX-A and RTX-S2 (Fig. 3) from R. macrodactylus were deduced from cDNA nucleotide sequences (Il'ina et al, 2005a(Il'ina et al, , 2005b(Il'ina et al, , 2006Monastyrnaya et al, 2010) and their have similar hemolytic activity on rabbit erythrocytes (~3.5 Â 10 4 HU/mg) (Table 1).…”
Section: Isoforms Of Actinoporins From Stichodactylidae Familymentioning
confidence: 99%